Identifikasi Senyawa Fenol Beberapa Aksesi Teki (Cyperus rotundus L.) serta Pengaruhnya terhadap Perkecambahan Biji Borreria alata (Aubl.) DC. - Dewi, Sangrani Annisa; Chozin, Muhammad Ahmad; Guntoro, dan Dwi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Purple nutsedge (Cyperus rotundus L.) is one of the important weeds in the world because of its ability to suppress the production of crops and difficult to control. C. rotundus residues can suppress the growth of others weeds. The experiments were conducted to identify the phenolic compound of C. rotundus from six different accessions and to determine the allelopathic effects of C. rotundus extracts on germination of Borreria alata (Aubl.) DC. The identification of phenolic compound was done using extract from all part of mature C. rotundus taken from different accessions and was analyzed using GC-MS. Analysis of C. rotundus extracts on germination of B. alata was designed using completely randomized design with three replications. The treatments were extract of C. rotundus from different accessions (from Cikarawang-Darmaga, Babakan-Darmaga, Ciawi, Megamendung, Cisarua, and Cianjur) with different concentration, 0.75 kg L-1 and 1.5 kg L-1. The result showed that C. rotundus from six accession had phenolic compond with different amounts. Cianjur accesion contained the most phenol content such as 2-furanmethanol; 1,4-benzenediol; 2-methoxy-4-vinylphenol; phenol, 2,6-dimethoxy; syringic acid; and 3-hydroxybenzoic acid. Germination test showed that C. rotundus extracts from different accessions and concentration had the same inhibitory effect on germination of B. alata.Keywords: Allelopathy, bioherbicide, purple nutsedge, weed management